-6+8r=-6+8r

Simple and best practice solution for -6+8r=-6+8r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+8r=-6+8r equation:


Simplifying
-6 + 8r = -6 + 8r

Add '6' to each side of the equation.
-6 + 6 + 8r = -6 + 6 + 8r

Combine like terms: -6 + 6 = 0
0 + 8r = -6 + 6 + 8r
8r = -6 + 6 + 8r

Combine like terms: -6 + 6 = 0
8r = 0 + 8r
8r = 8r

Add '-8r' to each side of the equation.
8r + -8r = 8r + -8r

Combine like terms: 8r + -8r = 0
0 = 8r + -8r

Combine like terms: 8r + -8r = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| S+26=8 | | x-6=-27 | | 0.2x+7.2=10 | | -3(2w-6)+4(-1-5w)=0 | | w*7*w*3*w=131 | | 40x^4-60x^3+20x=0 | | 5x-2=-3x+6 | | (3x+y)6= | | 5(y-2)-2=2(v+1)-5 | | 5B+3V=27.50 | | (x^2)-x-10=0 | | 4x^2+4=148 | | 5x-12-23x=6(-3x-2) | | 46-46x=(7x+3)(x-1) | | p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 |

Equations solver categories